2011
DOI: 10.1016/j.ajpath.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of MeCP2 in the Regulation of Myofibroblast Differentiation during Pulmonary Fibrosis

Abstract: DNA methylation is a key mechanism for repression of gene expression, including that of ␣-smooth muscle actin (␣-SMA) gene expression in fibroblasts. However, the trans-acting factors that interact with the methylated ␣-SMA gene to regulate its expression have not been identified. Using gel shift and chromatin immunoprecipitation (ChIP) assays, methyl CpG binding protein 2 (MeCP2) was shown to bind to the ␣-SMA gene. Suppression of MeCP2 gene expression by siRNA or its deficiency in lung fibroblasts isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 38 publications
5
76
0
1
Order By: Relevance
“…The same study also found that mice deficient in MeCP2 showed lesser levels of fibrosis when treated with bleomycin than was seen in the wild-type (Hu et al, 2011). In systemic sclerosis we have also seen elevated levels of MeCP2 in fibroblasts .…”
Section: Mecp2supporting
confidence: 59%
See 1 more Smart Citation
“…The same study also found that mice deficient in MeCP2 showed lesser levels of fibrosis when treated with bleomycin than was seen in the wild-type (Hu et al, 2011). In systemic sclerosis we have also seen elevated levels of MeCP2 in fibroblasts .…”
Section: Mecp2supporting
confidence: 59%
“…This indicates that MeCP2 acts as an activator of α-SMA expression. However, it was also found methylation of the α-SMA promoter region inhibited the stimulatory effect of MeCP2 (Hu et al, 2011).…”
Section: Mecp2mentioning
confidence: 97%
“…Suppression of MeCP2 expression in pulmonary fibroblasts increases αSMA expression which is a classical feature of myofibroblast differentiation. 26 Furthermore, in a bleomycin-induced pulmonary fibrosis model MeCP2 -/-displayed decreased pulmonary collagen deposition and decreased myofibroblast differentiation compared with wild type animals. 26 While MeCP2 can bind to unmethylated DNA, it is well recognized that it preferentially binds to methylated DNA to assist and promote chromatin remodeling.…”
Section: Epigenetics and Diseasementioning
confidence: 99%
“…26 Furthermore, in a bleomycin-induced pulmonary fibrosis model MeCP2 -/-displayed decreased pulmonary collagen deposition and decreased myofibroblast differentiation compared with wild type animals. 26 While MeCP2 can bind to unmethylated DNA, it is well recognized that it preferentially binds to methylated DNA to assist and promote chromatin remodeling. 27 Thus, several independent studies linking MeCP2 to myofibroblast differentiation all implicate alterations in DNA methylation at the heart of this process.…”
Section: Epigenetics and Diseasementioning
confidence: 99%
“…MeCP2 may be a generic core-regulator of tissue fibrosis since mecp2-deleted mice are also protected from pulmonary fibrosis. 38 MeCP2 operates two concurrent mechanisms to ensure epigenetic silencing of PPARc and HSC transdifferentiation. MeCP2 directly binds to methylCpG-rich regulatory regions in the PPARc promoter and recruits H3K9me3-modifying enzymes that suppress transcription initiation.…”
Section: Epigenetics and Liver Fibrosismentioning
confidence: 99%